Konsistensi dan Kepastian Kebijakan Investasi di Indonesia - Sidabutar, Amabel Yulia; Yusup, Mochamad Habbi; Victoria, Rain; Tantri, Raisya; Azzahra, Salma Putri; Astawa, I Ketut (Jurnal Ilmiah Wahana Pendidikan, 2025)
Investment is the activity of investing capital or money that is carried out to obtain a profit. someone who invests capital in a short period of time and a long period of time has their own benefits in the process of investing capital. the benefits obtained from investment are not like the salary of someone who works because the activities of this investment generate profits without having to do work. investment can be defined as the act or process of allocating a number of resources such as money, time, funds and effort in a stock of shares purchased in a company or asset and project projects that can be profitable in the future for investors. Investment decisions are the process of allocating investor funds by the management of a financial. investment can generate large profits in the future but in making investment decisions you must pay attention to goals, risks, market analysis, risk management and important actions, which must be considered in order to minimize losses that will occur. Investment decisions are one of the important factors that affect the value of a company.